Development guidelines for marketing mix Cultural tourism In Ratchaburi Province. - Silaswan, Kanokwan (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The purpose of this research is to: 1. Study tourism behavior, cultural tourism Ratchaburi province of tourists classified by personal characteristics.2. Study marketing mix factors That affects cultural tourism Ratchaburi Province and 3. Find ways to develop marketing mix Cultural tourism Ratchaburi Province. This research model uses a mixed method research methodology. Consisting of quantitative and qualitative research In the quantitative research, the sample group used in the research is Tourists based on cultural attractions in Ratchaburi Province, 400 people.Use the convenient sample selection Tools used for data collection include Questionnaires created by the researcher With content validity between 0.67 - 1.00, tested for reliability with Cronbach Alpha Coefficient. Found the confidence in the marketing mix with confidence in the range 0.72-0.86, while the tourism behavior had the confidence value of 0.88 Statistics used in data analysis were percentage, mean, standard deviation. Independent t-test One-way analysis of variance And multiple regression analysis For qualitative research Main contributor The researcher used a specific sample selection from People with experience in cultural tourism management And those involved and willing to cooperate in answering 3 questions. The research found that 1. Cultural tourism behavior in Ratchaburi Province will be different in education. And travel experience With statistical significance at 0.01 level 2. Marketing mix factors That affects cultural tourism Ratchaburi Province in the overall picture with forecasting power equal to 55 percent. The marketing mix factors affecting cultural tourism Ratchaburi Province In the overall picture Physical characteristics (b = 0.40), price (b = 0.26), personnel (b = 0.24) and products (b = 0.21) respectively. The predictive equation can be written as follows. Y = 1.72+ 0.21X1 *+ 0.26 X2 **+ 0.10 X3 + 0.11 X4 + 0.24 X5 **+ 0.04 X6 + 0.40 X7** 3. Guidelines for the development of marketing mix Cultural tourism Ratchaburi Province Requires understanding of the pulling factor and the pressure factor Let tourists be impressed. Come back again Including telling the impression of places to visit to people who know Is a development of marketing mix to sustainability With stakeholders having to focus on technology changes Creating a community identity And developing a model of local knowledge management along with. Article history : Received 30 Mar 2019 Revised 27 April 2019 Accepted 30 April 2019 SIMILARITY INDEX = 0.00